Stickhandling through the Margins : First Nations Hockey in Canada - Robidoux, Michael A. (Book collections on Project MUSE., 2012)
With stories and observations gleaned from three years of ethnographic research, Stickhandling through the Margins richly illustrates how hockey is played and experienced by First Nations peoples across Canada, both in isolated reserve communities and at tournaments that bring together participants from across the country. Robidoux's vivid description transports readers into the world of First Nations hockey, revealing it to be a highly social and at times even spiritual activity ripe with hidden layers of meaning that are often surprising to the outside observer."--Pub. desc.